Caracterização do componente não contrátil do tecido muscular e da resistência ao alongamento passivo em indivíduos hemiparéticos crônicos - Alcântara, Carolina Carmona de (2014)
Background: Muscle changes of paretic limb resulting from stroke lead to changes in the mechanical properties of muscles, such as muscle weakness and increased resistance to stretching. Studies that characterize the components of the muscle tissue, as the noncontractile, and biomarkers related to proliferation of connective tissue (such as TGF-β1 and myostatin) are clinically relevant and necessary for understanding of the resistance to stretching of paretic muscles. Therefore, the aim of this study was to evaluate the serum concentration of TGF-β1 and myostatin, the percentage volume of non-contractile tissue and passive peak torque and resistance to stretching (stiffness) of the extensor and flexor muscles of the knee in chronic hemiparesis. Methods: Cross-sectional study. Fourteen subjects with chronic hemiparesis post stroke and fourteen healthy paired-subjects participated in this study. Paretic, non-paretic and control limbs were evaluated. MRI images were obtained in all subjects and the percentage volume of non-contractile tissue of the quadriceps and hamstrings was measured. Serum TGF-β1 and myostatin concentrations were quantified by ELISA method. Passive torque peak and resistance during stretching (stiffness) of extensors and flexors muscles of knee were assessed at 60°/s using isokinetic dynamometer. Results: An increase in the percentage volume of non-contractile tissue in VM and VL of paretic limb compared to non-paretic limb was observed (p<0,05). Also, an increase was observed in the percentage volume of non-contractile tissue in SS in paretic limb compared to control limb (p<0,05). No differences were observed in serum TGF-β1 and myostatin concentrations in hemiparetic group compared to the control group (p> 0.05). Regarding passive torque, there was an increase in peak torque and resistance during passive stretching of extensor muscles with increasing ROM of paretic, non-paretic and control limbs (p<0,05), but no differences were found among limbs (p>0,05). In relation to flexor muscles, there was also an increase in peak torque along the ROM of the three limbs (p<0,05). However, non-paretic limb has lower values of peak torque than control and paretic limbs in lower ROM (p<0,05). Paretic limb increases resistance in a more accentuated pattern at intermediate ROM (50-40º) compared to control (p=0,02). A moderate correlation was observed between TGF-β1 serum concentration and flexor peak torque of paretic limb, considering complete ROM (p=0,01; r=0,736). Conclusion: Paretic muscles, extensors and knee flexors, although they have increased noncontractile tissue, exhibit similar resistance to stretching the muscles of healthy subjects. Knee flexor muscles of the non-paretic limbs have less passive stretch resistance compared to healthy subjects without changes in non-contractile content. Furthermore, no changes in serum concentrations of TGF-β1 and myostatin in chronic hemiparetic compared to healthy subjects were observed.